Ablution Practice Using the Jigsaw/Group Learning Strategy for Grade VII Students at Banpres Islamic Junior High School, Musi Rawas Regency, Odd Semester 2021/2022 - Eka Agus Welly Andi Ahsan Yunus (Jurnal Aghniya, 2024)
Background: The Islamic Jurisprudence (Fiqh) learning achievement of students at Banpres Islamic Junior High School remains low (70% passive). Conventional learning makes students bored and their motivation decreases. The Jigsaw strategy was chosen because it encourages active participation, individual responsibility, and group collaboration, making the ablution practice more meaningful.Method: Two-cycle CAR (Care Group Action Research), July 2021, with 10 seventh-grade students as subjects. The cycles were: planning (lesson plan, worksheets, ablution rubric), action (home-group, expert-group, and re-demonstration of ablution), observation, and reflection. Instruments: pre-test/post-test, observation sheets, interviews. Comparative analysis using paired t-test (α = 0.05).Results: Pre-test average 58; Post-test: Cycle I: 75 (t-count 4.24 > t-table 2.26), 70% completion; Cycle II: 87 (t-count 6.11), 90% completion. Psychomotor indicators achieved ≥85%; students gained more confidence, performed ablution movements in sequence, and used water sparingly. Teachers and students rated the learning as "enjoyable and easy to understand."Conclusion: Jigsaw effectively improves learning outcomes for ablution practice. Recommendations: use micro-skills videos, rotate expert roles, and monitor retention after 1 month to maintain skills.